Changing Cultures (Taylor & Francis, 2023)
The construction practices we employ in our daily life in European societies today were shaped by major changes in the past, such as the introduction and dissemination of Portland cement and reinforced concrete, a development that constitutes a fundamental chapter in the history of construction in the 19th and 20th centuries. Such changes were boosted by several innovations in the fields of applied mathematics, chemistry and physics. They involved patents licensing, optimization of materials production and machinery. There were new legislative frameworks, a specific knowledge transfer within a network of actors and the transformation of hierarchical frameworks.